Histological alterations found in the ureter during organ preservation and early phases of renal transplantation - Figueiredo, AJ (2005)
INTRODUCTION: There are no studies on the phenomena that occur on the ureter during organ preservation and immediately after transplantation. MATERIAL AND METHODS: We studied ureteral fragments obtained during organ harvesting in the cadaver (n = 9), after cold preservation period (n = 18), and immediately after kidney graft reperfusion (n = 126). In addition to the histological analysis, we evaluated the risk factors for the development of lesions and their relation to the evolution of the transplant. RESULTS: Alterations were detected in 120 of the 126 fragments studied after graft reperfusion. Global cellular infiltration was considered to be normal, mild, and moderate to severe in 34.9%, 41.3%, and 23.8%, respectively, consisting mainly of CD8(+) T lymphocytes. Urothelial exfoliation and cell vacuolization were detected in 42% and 52.4% of the cases, respectively. There was an inverse relationship between donor ventilation time and the intensity of the cellular infiltration. Seven and three of the nine fragments obtained during organ harvesting showed mild cellular infiltration of the chorion and urothelium, respectively. Cold storage promoted minor histological changes. After reperfusion, there was increased urothelial infiltration in 11 of the 18 cases. There was no relation between the lesions encountered and human leukocyte antigen compatibilities, renal rejections episodes, or the evolution of the graft itself. CONCLUSIONS: Consequences of brain death mechanical ventilation were detected at the ureteral level, with abnormal lymphocytic infiltration in most cases. Cold storage did not produce any major histological changes. The lesions detected after graft reperfusion do not seem to involve immunological phenomena.